The impact of implementing a consumption charge on carbon-intensive materials in Europe. (22nd April 2020) - Pollitt, Hector; Neuhoff, Karsten; Lin, Xinru
ABSTRACT: The production of basic materials accounts for around 25% of global greenhouse gas emissions. Existing measures to reduce emissions from industry are limited due to a combination of competitiveness concerns and a lack of technological options available to producers. In this paper, we assess the possibility of implementing a materials charge to reduce demand for basic industrial products and, hence, also reduce industrial emission levels. The modelling shows that a charge equivalent to around €80/tCO2 could reduce the EU's total (energy plus process) CO2 emissions by up to 10% by 2050, depending on the substitution options available. The materials charge could lead to small GDP increases and a minor reduction in overall employment levels. Key policy insights Full carbon price pass through along the materials value chain creates incentives for resource efficiency and substitution in the value chain of material use. Most macroeconomic models ignore mitigation opportunities in the value chain, as do carbon pricing mechanisms for industrial emitters, which largely mute incentives for mitigation opportunities with free allowance allocation. Including consumption at a benchmark level in emission trading systems reinstates a full carbon price incentive for all mitigation opportunities while avoiding competitive distortions and carbon leakage risks. Macroeconomic modelling shows that this allows for an additional 10% emission reduction accompanied by a slight GDP increase and employment reduction. Long-term clarity on carbon leakage protection furthermore strengthens low-carbon investment frameworks.